2022
DOI: 10.1039/d2lc00540a
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional micromodels for studying the convective dissolution of carbon dioxide in 2D water-saturated porous media

Abstract: Convective dissolution is a perennial trapping mechanism of carbon dioxide in geological formations saturated with an aqueous phase. This process, which couples dissolution of supercritical CO2, convection of the liquid...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…With respect to the design and production of synthetic media at the laboratory scale, microfluidic devices mimicking porous materials are usually made of polydimethylsiloxane (PDMS), which has the drawback of being permeable to CO . A solution has been recently proposed by De et al [ 137 ], who developed a new method to fabricate a two-dimensional porous medium (regular array of cylinders), consisting of bonding of a patterned photo-lithographed layer on a flat base. Additional examples of manufacturing techniques for analogue porous media are provided in [ 138 ].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…With respect to the design and production of synthetic media at the laboratory scale, microfluidic devices mimicking porous materials are usually made of polydimethylsiloxane (PDMS), which has the drawback of being permeable to CO . A solution has been recently proposed by De et al [ 137 ], who developed a new method to fabricate a two-dimensional porous medium (regular array of cylinders), consisting of bonding of a patterned photo-lithographed layer on a flat base. Additional examples of manufacturing techniques for analogue porous media are provided in [ 138 ].…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…The nature of this transition in pore-resolved flows has not been explored yet, and in the future it will be of interest to extend the present study to simulations in three dimensions, as well as two-dimensional experiments (De et al. 2022), to allow for a one-to-one comparison of these findings and to investigate the effect of the dimensionality of the flow on the evolution of a pore-resolved system. At the pore scale, three-dimensionality provides more pathways for fingers to percolate through, and the interfacial area of three-dimensional fingers will be greater than for two-dimensional fingers.…”
Section: Summary Conclusion and Outlookmentioning
confidence: 95%
“…The absorbance of the indicator in a strong acid or strong alkali environment can be expressed by the following equations ( 23) (24) where c is the concentration of the pH indicator. Using the extreme absorbance values and eqs 20−22, the following equation is derived (25) where is the absorbance factor, which varies proportionally with the solution pH. By adding different concentrations of hydrochloride acid or sodium hydroxide, the pH of the experimental solution was varied within the functional range of the pH indicator, and the corresponding absorbance factor was calculated, as presented in Figure 14.…”
Section: Vertical Progression Of Fingersmentioning
confidence: 99%
“…The Hele–Shaw cell, a simple apparatus built with a small aperture between two transparent flat plates, has been extensively used to visualize the Darcy flow, including density-driven CO 2 transport. Furthermore, by varying several parameters in the cell, such as aperture, porosity, and vertical or horizontal permeability, it is possible to mimic the transport mechanism similar to that of CO 2 storage in different geological structures. These experimental studies have adopted different visualization techniques to investigate the finger morphology during density-driven CO 2 transport, such as the pH indicator-based method, Schlieren method, particle image velocimetry, laser-induced fluorescence, and interferometry method. ,, Furthermore, several studies have investigated scaling relationships to characterize the convective dissolution rate of CO 2 in brine formations. Mojtaba et al developed a relationship between Sherwood and Rayleigh numbers and CO 2 convective flux at different Rayleigh numbers under 3.45 MPa and 182 < Ra < 20,860. Mahmoodpour et al showed scaling relationships between compensated flux and transition times between successive regimes in the system for experimental fluid with different salt types (NaCl and CaCl 2 ).…”
Section: Introductionmentioning
confidence: 99%